M-Learning: Content Tool for Accounting - MUHAMAD, MUHAMAD FADZRIL (Universiti Teknologi Petronas, 2006)
Independency of time and space are often named as the main advantages of e-Learning. The basic requirement of e-Learning is a Personal Computer (PC), and therefore a real independency of time and space is not given. Even with a notebook these independencies are not fulfilled, because a real independency of time and space means learning wherever and whenever you want to learn. Hardly anyone carries his notebook or his PC with him all the time. Due to certain requirements eLearning fulfils just partly this demand of independency. Mobile learning (MLearning), the next generation of the computer-aided and multimedia-based learning, is based on mobile phones. The market penetration of mobile phones in Malaysia is at a level of 81% and the numbers are rising. It can be said, that the great majority of the population has a mobile phone and carries it with them most of the time. Because of this fact the independency of time and space for learning is fulfilled to nearly a hundred percent. As a consequence the main advantage of mobile learning is learning wherever and whenever you want to learn. You can use idle periods for learning. For example: The times while you are traveling, while you are waiting for the bus or while you are waiting at the restaurant or at the trainstation. Nearly every unused and wasted time can now be used for efficient and effective learning. Therefore mobile learning will be an important instrument for lifelong learning, because it will help us to use our time more efficiently.